Analisis Perilaku dan Preferensi Konsumen Generasi Z pada Toko Online di Era Digital (Studi Kasus : Shopee) - Laila Alfi Syahrillah (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the behavior and preferences of Generation Z consumers in online shopping activities in the digital era, using the Shopee e-commerce platform as a case study. As digital natives, Generation Z exhibits unique characteristics, such as a tendency toward impulsive buying, high responsiveness to discount programs, and a preference for shopping experiences that are fast, practical, and enjoyable. Through a literature review using a descriptive-analytical approach, this study finds that Generation Z’s shopping behavior is influenced by application ease of use, transaction speed, various promotional offers, flash sales, and extensive exposure to information on social media. Furthermore, their preference for Shopee is driven by the platform’s user-friendly interface, secure payment system, interactive features such as live shopping, user reviews, and the integration of digital wallet services that streamline the checkout process. The analysis reveals that Shopee’s success in attracting and retaining young consumers is strongly influenced by its ability to tailor digital marketing strategies to the psychological characteristics and consumption patterns of Generation Z. These findings are expected to serve as a reference for businesses and marketers in designing more effective, relevant, and adaptive marketing strategies that align with the dynamics of today’s digital consumers.